2008
DOI: 10.1080/10640260801887303
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Disordered Eating Behaviors among Israeli Adolescent Girls

Abstract: Eating behaviors were assessed by a modified SCOFF questionnaire in a National representative cross-sectional study among 2978 Israeli schoolgirls. The mean age was 14.7. Thirty percent met the criteria for disordered eating. Being Jewish or underweight reduced the odds for disordered eating. The following increased the risk: dieting, early onset of menarche, being overweight or obese, and suffering from constipation. School socio-economic status, physical activity, and smoking status were not contributory. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 20 publications
3
30
0
1
Order By: Relevance
“…However, at T2 (six months later), significantly more female than male subjects reported that they had lost control over how much they ate (symptom for bine-eating disorder). In agreement, the prevalence of binge-eating disorder was also reported to be high among Israeli adolescent girls (Kaluski, Natamba, Goldsmith, Shimony, & Berry, 2008). Chia et al (2002) reported that binge eating disorder was highly prevalent among Singaporean adults, more prevalent that AN or BN and deserves greater research attention in terms of its aetiology and treatment.…”
Section: Discussionsupporting
confidence: 56%
“…However, at T2 (six months later), significantly more female than male subjects reported that they had lost control over how much they ate (symptom for bine-eating disorder). In agreement, the prevalence of binge-eating disorder was also reported to be high among Israeli adolescent girls (Kaluski, Natamba, Goldsmith, Shimony, & Berry, 2008). Chia et al (2002) reported that binge eating disorder was highly prevalent among Singaporean adults, more prevalent that AN or BN and deserves greater research attention in terms of its aetiology and treatment.…”
Section: Discussionsupporting
confidence: 56%
“…These prevalence rates are within the range found in previous research. Specifically, reported prevalence rates for girls vary from 30 % among Israeli girls ( M age  = 14.7; [23]) to 52 % among Finnish girls ( M age  = 14.9; [18]) as well as 56 % of girls in a large sample (over 40,000) of 9th and 12th grade American female adolescents (Croll et al, 2002). The prevalence rates of DE for boys have been found to vary as well, at 15 % as reported by Herpertz-Dahlmann et al [20] in a German sample of 1,895 11- to 17-year-old adolescents; 17 % as reported by Hautala et al [18] in a Finnish sample of adolescent boys aged 15; 25 % as reported by Lavender et al [26] in a study of male undergraduates; and 29 % as reported by Croll et al (2002) among American adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Os principais termos usados para caracterizar a presença de comportamentos de risco para TA foram "risco de transtornos alimentares" 13,[27][28][29][30]34,38,52,60,67,[77][78][79]81,82,88 e "comer transtornado" 35,39,41,[43][44][45][46]48,63,65,68,73,84,86 . Mesmo assim, mais de 60% dos estudos utilizaram outras diversas nomenclaturas e, no contexto do Brasil, observa-se que também não há padronização dos termos.…”
Section: Discussionunclassified